Enhancing student access to science curricula through a reading intervention. Issue 4 (11th February 2019) - Saqui, Sonja; Mercer, Sterett H.; Cheng, Michèle P.
Abstract: The current study explored whether a reading intervention combining flexibly applied multisyllabic word‐decoding strategies with evidence‐based fluency strategies was effective in improving the science text reading skills of upper‐elementary struggling readers. Four students, three in fourth and one in fifth grade, participated in the study. A delayed multiple baseline design was utilized, with a staggered 3‐week baseline followed by 8 weeks of reading intervention. Three students demonstrated small to moderate gains in reading fluency on science instructional passages, but no generalized gains in reading fluency on standardized passages. All students demonstrated direct gains in multisyllabic word‐decoding accuracy on science instructional passages, but no generalized gains in decoding accuracy on standardized passages. Participating students rated the intervention favorably and perceived gains in their reading skills. These findings support the use of science curricular passages when implementing reading interventions to enhance students' ability to access the curriculum.